Phytochemical studies and antioxidant activity of two South African medicinal plants traditionally used for the management of opportunistic fungal infections in HIV/AIDS patients - Otang Wilfred; Grierson Donald; Ndip Roland (BMC, 2012)
Abstract Background It has been observed that perturbations in the antioxidant defense systems, and consequently redox imbalance, are present in many tissues of HIV-infected patients. Hence, the exogenous supply of antioxidants, as natural compounds that scavenge free radicals, might represent an important additional strategy for the treatment of HIV infection. The aim of this study was therefore to analyse the phytochemical constituents and antioxidant potential of Gasteria bicolor Haw and Pittosporum viridiflorum Sims., two South African plants traditionally used for the management of opportunistic fungal infections (OFIs) in AIDS patients. Methods The in vitro antioxidant properties of the two plants were screened through DPPH (1,1-diphenyl-2-picrylhydrazyl), NO (nitric oxide), H2O2 (hydrogen peroxide) radical scavenging effects and reducing power assays. Phytochemical studies were done by spectrophotometric techniques. Results There were no significant differences in the flavonoid and proanthocyanidins contents between the leaves and bark extracts of Gasteria bicolor and Pittosporum viridiflorum respectively, while the total phenolic content of the bark extract of P. viridiflorum was significantly higher than that of G. bicolor leaf. The acetone extracts of both plants indicated strong antioxidant activities. Conclusion The results from this study indicate that the leaves and stem extracts of Gasteria bicolor and Pittosporum viridiflorum respectively possess antioxidant properties and could serve as free radical inhibitors, acting possibly as primary antioxidants. Since reactive oxygen species are thought to be associated with the pathogenesis of AIDS, and HIV-infected individuals often have impaired antioxidant defenses, the inhibitory effect of the extracts on free radicals may partially justify the traditional use of these plants in the management of OFIs in HIV patients in South Africa.